A role for neurokinin-1 receptor neurons in the rostral ventromedial medulla in the development of chronic postthoracotomy pain. Issue 7 (July 2017) - Khasabov, Sergey G.; Wang, Jeffrey Chi-Fei; Simone, Donald A.; Strichartz, Gary R.
Abstract : Abstract: Thoracotomy results in chronic postoperative pain (CPTP) in half of the cases. Earlier findings in rat models of persistent post-surgical pain suggest that spinal pathways are critical for pain onset but not its maintenance. Descending systems from the brain stem modulate nociceptive transmission in the spinal cord and contribute to persistent pain, but their role in chronic postoperative pain has not been studied. Here, we ablated pronociceptive neurokinin-1 receptor (NK-1R)-expressing neurons in the rat rostral ventromedial medulla (RVM) to identify their role in CPTP. Cells were ablated by microinjection of the neurotoxin Sar 9, Met(O2 ) 11 -Substance P (SSP-SAP), either 2 to 3 weeks before ("Prevention" condition) or 10 days after ("Reversal" condition) thoracotomy with rib retraction. Inactive Blank-SAP was the control. Tactile hypersensitivity was defined by lowered force thresholds for nocifensive responses to von Frey filaments applied over the dorsal trunk, and pain-like behavior assessed by the Qualitative Hyperalgesia Profile; both were followed for 5 weeks after surgery. SSP-SAP injection before surgery resulted in ∼95% loss of NK-1R neurons in RVM and prevented postoperative mechano-hypersensitivity. Blank-SAP was ineffective. SSP-SAP given at postoperative day 10 was equally effective in ablating NK-1R neurons but fully reversed mechano-hypersensitivity in only 3 of 9 hypersensitive rats. Fewer rats showed intense pain-like behavior, by Qualitative Hyperalgesia Profile analysis, in the Prevention than in the Control conditions, and the more intense pain behaviors declined along with SSP-SAP-induced Reversal of hypersensitivity. Neurokinin-1 receptor-expressing neurons in RVM appear essential for the development but contribute only partially to the maintenance of CPTP. Abstract : Neurokinin-1 receptor-expressing neurons in the rostral ventromedial medulla are essential for the development of chronic postthoracotomy pain but only partially contribute to the maintenance of this pain.